Team science: A syllabus for success on big projects - Delaney M. Peterson; Sarah M. Flynn; Riley S. Lanfear; Chelsea Smith; Logan J. Swenson; Alice M. Belskis; Stephen C. Cook; Christopher T. Wheeler; Jessica F. Wilhelm; Amy J. Burgin (Ecology and Evolution, 2023)
Abstract Interdisciplinary teams are on the rise as scientists attempt to address complex environmental issues. While the benefits of team science approaches are clear, researchers often struggle with its implementation, particularly for new team members. The challenges of large projects often weigh on the most vulnerable members of a team: trainees, including undergraduate students, graduate students, and post‐doctoral researchers. Trainees on big projects have to navigate their role on the team, with learning project policies, procedures, and goals, all while also training in key scientific tasks such as co‐authoring papers. To address these challenges, we created and participated in a project‐specific, graduate‐level team science course. The purposes of this course were to: (1) introduce students to the goals of the project, (2) build trainees' understanding of how big projects operate, and (3) allow trainees to explore how their research interests dovetailed with the overall project. Additionally, trainees received training regarding: (1) diversity, equity & inclusion, (2) giving and receiving feedback, and (3) effective communication. Onboarding through the team science course cultivated psychological safety and a collaborative student community across disciplines and institutions. Thus, we recommend a team science course for onboarding students to big projects to help students establish the skills necessary for collaborative research. Project‐based team science classes can benefit student advancement, enhance the productivity of the project, and accelerate the discovery of solutions to ecological issues by building community, establishing a shared project vocabulary, and building a workforce with collaborative skills to better answer ecological research questions.